Ameliorative effects of riboflavin on acetic acid‐induced colonic injury in rats. (27th December 2017) - Karakoyun, Berna; Ertaş, Büşra; Yüksel, Meral; Akakın, Dilek; Çevik, Özge; Şener, Göksel
Summary: Riboflavin (RF) has been found to be a promising antioxidant and/or anti‐inflammatory agent in several studies. However, the effect of RF against acetic acid (AA)‐induced colonic injury is currently unknown. This study aimed to investigate the potential antioxidant and protective effects of RF in a rat model of ulcerative colitis. Starting immediately after the colitis induction (AA+RF group) or 1 week before the colitis induction (RF+AA+RF group), the rats were treated with RF (25 mg/kg per day; p.o.) for 3 days. The control and AA groups received saline (1 mL; p.o.) whereas AA+SS group (positive control) received sulfasalazine (100 mg/kg per day; p.o.) for 3 days. Colonic samples were taken for the biochemical and histological assessments on the third day. High damage scores, elevated tissue wet weight index (WI), tissue myeloperoxidase (MPO) activity, 8‐hydroxy‐2′‐deoxyguanosine levels and chemiluminescence values, and a pronounced decrease in antioxidant glutathione (GSH) levels of the AA group were all reversed by RF pretreatment (RF+AA+RF group) and SS treatment (AA+SS group) ( P  <   .05‐.001). Tissue WI, MPO activity and GSH levels were not statistically changed in the AA+RF group. Western blot analysis revealed that the decreased protein expressions of tissue collagen (COL) 1A1, COL3A1 and transforming growth factor‐β1 in the AA group were elevated in all the treatment groups ( P  < .05‐.001). In conclusion, RF exerts both the antioxidant and anti‐inflammatory effects against AA‐induced colonic inflammation by suppressing neutrophil accumulation, inhibiting reactive oxidant generation, preserving endogenous glutathione, improving oxidative DNA damage and regulating inflammatory mediators, suggesting a future potential role in the treatment and prevention of ulcerative colitis.